SANDFLIES OF ILAM PROVINCE, WEST OF IRAN WITH DESCRIPTION OF TWO NEW SPECIES FROM THE GENUS PHLEBOTOMUS: PH. ILAMI AND PH. NADIMI. - E. Javadian; A. Jalali-Galousang; Seyedi-Rashti (Tehran University of Medical Sciences, 1997)
During the period of April to November 1994, an investigation was carried out on fauna of Phlebotominac in Ilam province, west of Iran. About 12000 sandflies were caught by sticky trap, light trap and aspirator from different ecological regions and were identified. These sandflies consist of 22 species (11 species from the genus Phlebotomus: Ph. paptasi, Ph.sergenti, Ph.alexandri, Ph.rnajor, Ph.tobbi, Ph.kandelakii, ph.perfiliewi. Ph.balcanicus and Ph.halepensis plus two new species of Phlebotomus and 11 species from the genus Sergentomyia: S. sintoni, S.dentata, S.antennata, S.theodori, S.mervynae, S.pawlowskyi, S.africana, S.clydei , S.tiberiadis , S.iranica and S.squatnipleurs). The two new species from genus Phlebotomus (Ph.nadimi and Ph.ilami) found in this study have been described in detail.